2013
DOI: 10.1111/cas.12229
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution imaging mass spectrometry reveals detailed spatial distribution of phosphatidylinositols in human breast cancer

Abstract: High-resolution matrix-assisted laser desorption ⁄ ionization imaging mass spectrometry (MALDI IMS) is an emerging application for lipid research that provides a comprehensive and detailed spatial distribution of ionized molecules. Recent lipidomic approach has identified several phospholipids and phosphatidylinositols (PIs) are accumulated in breast cancer tissues and are therefore novel biomarker candidates. Because their distribution and significance remain unclear, we investigated the precise spatial distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…Results showed that several PIs were specifically localized into cancer cell clusters, with a heterogeneous distribution, which identified two different populations of cancer cells: the first predominantly expressed PI 18:0/18:1, the second PI 18:0/20:3. Moreover, the latter population was associated with tumor invasion [54]. …”
Section: Lipidomics In Cancer Researchmentioning
confidence: 99%
“…Results showed that several PIs were specifically localized into cancer cell clusters, with a heterogeneous distribution, which identified two different populations of cancer cells: the first predominantly expressed PI 18:0/18:1, the second PI 18:0/20:3. Moreover, the latter population was associated with tumor invasion [54]. …”
Section: Lipidomics In Cancer Researchmentioning
confidence: 99%
“…PC levels and total choline-containing PL metabolite levels were found to be increased in human breast cancer epithelial cells (Williams & Maunder, 1993). PI levels were also increased in some breast, lung, ovarian, prostate, and gastric cancer tissues (Ringel et al, 2001;Altomare et al, 2004;Dill et al, 2009;Yan et al, 2009;Kawashima et al, 2013;Liao et al, 2013). PIs involve the PI3kinase pathway, which regulates many cellular functions, including lipid metabolism, which is frequently mutated or activated in breast cancer tissues (Miller, Balko, & Arteaga, 2011;Network, 2012).…”
Section: Pls In Various Cancersmentioning
confidence: 99%
“…IMS was previously used to analyze intracellular phospholipids (Shimma et al, 2007;Snel and Fuller, 2010;Miyamura et al, 2011;Kawashima et al, 2013;Goto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Buck et al (2015) and Groseclose et al (2015) reported localization of SN-38, which is an active metabolite of a colon cancer drug, and deposition of dabrafenib in renal tubules from a toxicological study, respectively. Furthermore, a comparison of endogenous substrates between normal and tumorous tissues (Shimma et al, 2007;Kawashima et al, 2013;Goto et al, 2014), and changes in the endogenous substrates in response to drugs were also examined by IMS (Sun et al, 2016). Therefore, it is possible to evaluate susceptibility to DIPL by distinguishing mouse and human hepatocyte regions on the liver slices prepared from chimeric mice after the administration of amiodarone and analyzing hepatic localization of amiodarone, desethylamiodarone, and PhCs by IMS.…”
Section: Introductionmentioning
confidence: 99%